2013
DOI: 10.1097/sle.0b013e3182827e51
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study of Systemic Inflammation and Immune Response After Laparoscopic Nissen Fundoplication Performed With Standard and Low-pressure Pneumoperitoneum

Abstract: This study demonstrated that reducing the pressure of the pneumoperitoneum to 6 to 8 mm Hg during LNF is reduced p.o. inflammatory response and avoided p.o. immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 73 publications
2
20
0
Order By: Relevance
“…The disturbance, traction and the compression of the thoracic cavity by pneumoperitoneum during surgery are the important elements of trauma 28 . Studies have demonstrated that trauma is closely associated with the stability of the internal environment 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The disturbance, traction and the compression of the thoracic cavity by pneumoperitoneum during surgery are the important elements of trauma 28 . Studies have demonstrated that trauma is closely associated with the stability of the internal environment 29 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…A possible cause of higher levels of cortisol, ACTH and aldosterone may be the pneumoperitoneum, which is previously known to initiate an inflammatory reaction [28,29] and hormonal stress response [30][31][32]. The increase in these hormones is measurable after only a few minutes after the introduction of pneumoperitoneum, and stays high during the pneumoperitoneum time.…”
Section: Outcomes and Estimationmentioning
confidence: 99%
“…A recent pilot study performed by our group has shown that low pressure pneumoperitoneum (7 mmHg) was feasible and significantly reduced postoperative pain scores during the first 72 hours after surgery [ 7 ]. Others have shown that low pressure pneumoperitoneum in other laparoscopic procedures is associated with a reduction of post-operative pain and analgesic consumption [ 8 10 ]. However, low pressure pneumoperitoneum was also associated with longer operation time, probably due to less optimal perioperative visibility.…”
Section: Introductionmentioning
confidence: 99%